Targeting p62 by sulforaphane promotes autolysosomal degradation of SLC7A11, inducing ferroptosis for osteosarcoma treatment - Qiuming Zou; Xiaofeng Zhou; Jianqin Lai; Haixia Zhou; Jinxuan Su; Zhijing Zhang; Xiaosong Zhuang; Lili Liu; Ruijie Yuan; Sijia Li; Siyu Yang; Xinyi Qu; et al. (Redox Biology)
Osteosarcoma (OS) is the most prevalent malignant bone tumor in children and adolescents worldwide. Identification of novel therapeutic targets and development of targeted drugs are one of the most feasible strategies for OS treatment. Ferroptosis, a recently discovered mode of programmed cell death, has been implicated as a potential strategy for cancer therapy. Sulforaphane (SFN), the main bioactive compound derived from cruciferous vegetables, has shown potential anti-cancer effects with negligible toxicity. However, the role of ferroptosis in the effect of SFN on OS remains unknown. In the present study, we found that SFN acted as a potent ferroptosis inducer in OS, which was demonstrated by various inhibitors of cell death. The SFN-induced ferroptotic cell death was characterized by elevated ROS levels, lipid peroxidation, and GSH depletion, which was dependent on decreased levels of SLC7A11. Mechanically, SFN directly targeted p62 protein and enhanced p62/SLC7A11 protein-protein interaction, thereby promoting the lysosomal degradation of SLC7A11 and triggering ferroptosis. Notably, both subcutaneous and intratibial OS models in nude mice confirmed the ferroptosis associated anti-cancer efficacy of SFN in vivo. Hence, our findings demonstrate that SFN exerts its anti-cancer effects through inducing SLC7A11-dependent ferroptosis in OS, providing compelling evidence for the application of SFN in OS treatment.